Gap‐Mode Surface‐Plasmon‐Enhanced Photoluminescence and Photoresponse of MoS2 - Wu, Zhi‐Qian; Yang, Jing‐Liang; Manjunath, Nallappagar K.; Zhang, Yue‐Jiao; Feng, Si‐Rui; Lu, Yang‐Hua; Wu, Jiang‐Hong; Zhao, Wei‐Wei; Qiu, Cai‐Yu; Li, Jian‐Feng; Lin, Shi‐Sheng (Advanced materials (Weinheim), 2018)
2D materials hold great potential for designing novel electronic and optoelectronic devices. However, 2D material can only absorb limited incident light. As a representative 2D semiconductor, monolayer MoS2 can only absorb up to 10% of the incident light in the visible, which is not sufficient to achieve a high optical‐to‐electrical conversion efficiency. To overcome this shortcoming, a “gap‐mode” plasmon‐enhanced monolayer MoS2 fluorescent emitter and photodetector is designed by squeezing the light‐field into Ag shell‐isolated nanoparticles–Au film gap, where the confined electromagnetic field can interact with monolayer MoS2. With this gap‐mode plasmon‐enhanced configuration, a 110‐fold enhancement of photoluminescence intensity is achieved, exceeding values reached by other plasmon‐enhanced MoS2 fluorescent emitters. In addition, a gap‐mode plasmon‐enhanced monolayer MoS2 photodetector with an 880% enhancement in photocurrent and a responsivity of 287.5 A W−1 is demonstrated, exceeding previously reported plasmon‐enhanced monolayer MoS2 photodetectors. By dropping Ag shell‐isolated nanoparticles onto Al2O3‐covered Au film, the gap‐mode plasmonic structure with a gap thickness of 7 nm can form naturally. By integrating monolayer MoS2 into this plasmonic structure, 110‐fold photoluminescence and 880% photocurrent enhancement are achieved. This work shows that the gap‐mode plasmonic structures have huge potential for realizing high‐performance 2D‐material‐based optoelectronic devices.